2013
DOI: 10.1161/circulationaha.112.000679
|View full text |Cite
|
Sign up to set email alerts
|

Vorapaxar in Patients With Peripheral Artery Disease

Abstract: Background— Vorapaxar is a novel antagonist of protease-activated receptor-1, the primary receptor for thrombin on human platelets that is also present on vascular endothelium and smooth muscle. Patients with peripheral artery disease are at risk of systemic atherothrombotic events, as well as acute and chronic limb ischemia and the need for peripheral revascularization. Methods and Results— The Trial to Assess the Effects of SCH 530348 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(87 citation statements)
references
References 26 publications
1
78
0
8
Order By: Relevance
“…In patients from TRA 2°P with peripheral vascular disease, vorapaxar reduced hospitalization as a result of acute limb ischemia (2.3% with vorapaxar, 3.9% with placebo, P=0.006) and peripheral artery revascularization (18.4% with vorapaxar, 22.2% with placebo, P=0.017). Bleeding was more frequent in patients taking vorapaxar (7.4% with vorapaxar, 4.5% with placebo, P=0.001) [73]. Diabetics participating in the TRA 2°P trial demonstrated additional benefit with regard to the primary endpoint of cardiovascular death, MI, or cerebrovascular accident (12.6% with vorapaxar, 15.7% with placebo, P=0.004).…”
Section: Indications For Par1 Modulationmentioning
confidence: 99%
“…In patients from TRA 2°P with peripheral vascular disease, vorapaxar reduced hospitalization as a result of acute limb ischemia (2.3% with vorapaxar, 3.9% with placebo, P=0.006) and peripheral artery revascularization (18.4% with vorapaxar, 22.2% with placebo, P=0.017). Bleeding was more frequent in patients taking vorapaxar (7.4% with vorapaxar, 4.5% with placebo, P=0.001) [73]. Diabetics participating in the TRA 2°P trial demonstrated additional benefit with regard to the primary endpoint of cardiovascular death, MI, or cerebrovascular accident (12.6% with vorapaxar, 15.7% with placebo, P=0.004).…”
Section: Indications For Par1 Modulationmentioning
confidence: 99%
“…Role of Platelets PAR-1 inhibitors; that is, patients with prior MI. 119 Even in prior MI patients, those with diabetes were shown to be the most appropriate patient population for vorapaxar. 59 The clinical development of vorapaxar and the assessment of the data by the US regulatory authority 120 give us a clue to the selection of suitable small populations of patients for new drug interventions within the database of large-scale global trials in the future.…”
Section: Thrombin Receptor Antagonists and Anticoagulantsmentioning
confidence: 99%
“…In an analysis excluding such patients (n=14,909), known as a low-bleeding-risk cohort, the primary combined ischemic end point was significantly reduced with vorapaxar compared with placebo (6.8% versus 8.6%, HR 0.75, 95% CI 0.66–0.85; P <0.0001), and there was also a significant reduction in cardiovascular death (1.5% versus 2.0%, HR 0.73, 95% CI 0.56–0.95; P =0.02). GUSTO moderate or severe bleeding was lower than in the overall trial, although still higher with vorapaxar than placebo (2.7% versus 1.8%) 59. Overall, this analysis conducted among patients who were randomized in the TRA 2°P trial indicates that among appropriately selected patients, prolonged treatment with vorapaxar when added to aspirin with or without a thienopyridine may be beneficial for long-term secondary prevention in patients with prior MI.…”
Section: Tra 2°p – Timi 50mentioning
confidence: 67%
“…Vorapaxar failed to reduce the primary efficacy end point compared with placebo (11.3% versus 11.9%, HR 0.94, 95% CI 0.78–1.14; P =0.53) 59. However, vorapaxar did reduce the rate of hospitalization for acute limb ischemia (2.3% versus 3.9%, HR 0.58, 95% CI 0.39–0.86; P =0.006) and peripheral artery revascularization (18.4% versus 22.2%, HR 0.84, 95% CI 0.73–0.97; P =0.017).…”
Section: Tra 2°p – Timi 50mentioning
confidence: 90%